2018
DOI: 10.3389/fpsyg.2017.02295
|View full text |Cite
|
Sign up to set email alerts
|

Self-presentation in Online Professional Networks: Men's Higher and Women's Lower Facial Prominence in Self-created Profile Images

Abstract: Men are presented with higher facial prominence than women in the media, a phenomenon that is called face-ism. In naturalistic settings, face-ism effects could be driven by gender biases of photographers and/or by gender differences in self-presentation. The present research is the first to investigate whether women and men themselves create this different facial prominence. In a controlled laboratory study, 61 participants prepared a picture of themselves from a half-body photograph, allegedly to be uploaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The more variables are included to study face-ism, the more complex seems to be the phenomenon. In this line, it might explain the not significant differences found in previous studies, focused on only one SNS or in a narrower range of age (mainly, young people) (for instance, Hum et al, 2011 andKaufmann, 2018, focused on young people on Facebook and professional networks, respectively). The sex-gender construction is developed across biological, psychological, and social dimensions and is transformed through life experiences and learning.…”
Section: Theoretical Contributionsmentioning
confidence: 87%
See 1 more Smart Citation
“…The more variables are included to study face-ism, the more complex seems to be the phenomenon. In this line, it might explain the not significant differences found in previous studies, focused on only one SNS or in a narrower range of age (mainly, young people) (for instance, Hum et al, 2011 andKaufmann, 2018, focused on young people on Facebook and professional networks, respectively). The sex-gender construction is developed across biological, psychological, and social dimensions and is transformed through life experiences and learning.…”
Section: Theoretical Contributionsmentioning
confidence: 87%
“…Since the late 1970s, numerous studies have provided evidence of differences in the representation of women and men in pictures (Adams, Copeland, Fish & Hughes, 1980;Archer, Iritani, Kimes & Barrios, 1983;Copeland, 1989;Millard & Grant, 2006;Patton & Johns, 2007;Sczesny & Kaufmann, 2018), particularly in fields such as advertising (Belkaoui & Belkaoui, 1976;Furnham & Bitar, 1993;Ganahl, Prinsen & Netzley, 2003), politics (Konrath, Au & Ramsey, 2012;Konrath & Schwartz, 2007), and the internet (Szillis & Stahlberg, 2007). Whereas in men's pictures the focus is mainly on their faces (facial prominence), in women's pictures it is on their bodies (body prominence); they both correspond to social stereotypes which associate men with the mind and women with the body.…”
Section: Introductionmentioning
confidence: 99%
“…This strongly points to an internalization of gender stereotypes and to what has been called “self-inflated face-ism” ( Smith and Cooley, 2012 ). This effect emerged also in a controlled laboratory study in which male and female participants were allowed to digitally modify their photographs to be allegedly posted in an online professional network ( Sczesny and Kaufmann, 2018 ).…”
Section: Introductionmentioning
confidence: 96%
“…
This paper aims to investigate the influence of relevant factors on the personal promotion of businessoriented social network users. Motivation: Although personal promotion in online communities has been covered in academic literature (Sczesny & Kaufmann, 2018;Yu & Kim, 2020;Hollenbaugh, 2020), a significant gap in previous studies is found in neglecting influential factors on self-promotion through a business-oriented social network, such as LinkedIn. Therefore, this paper aims to explore LinkedIn users' opinions about the impact of selected constructs on this businessoriented social network setting.
…”
mentioning
confidence: 99%